2007
DOI: 10.1510/icvts.2006.146928
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lateral tunnel and extracardiac conduit Fontan procedure

Abstract: Comparison of lateral tunnel and extracardiac conduit Fontan procedurehttp://icvts.ctsnetjournals.org/cgi/content/full/6/3/328 located on the World Wide Web at:The online version of this article, along with updated information and services, is AbstractThe purpose of this study was to compare the outcomes of lateral tunnel (LT) and extracardiac conduit (ECC) Fontan procedures at a single institution. From April 1995 to December 2006, 165 Fontan procedures were performed (67 LT, 98 ECC). Pre-, intra-and postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Based on the several clinical, in vivo and in vitro flow studies,19 two contemporary surgical templates, namely intra-atrial lateral tunnel and extra-cardiac TCPC are now the current final-stage (S3R) surgical procedures of choice 1,28,48. The hemodynamic advantage of one surgical template type over the other is a critical long-asked clinical question 11,29. However a definite conclusion is challenged due to patient-to-patient variations in congenital heart disease, univentricle heart function,50 preload, afterload, pulmonary, hepatic venous physiology, and respiratory pump.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the several clinical, in vivo and in vitro flow studies,19 two contemporary surgical templates, namely intra-atrial lateral tunnel and extra-cardiac TCPC are now the current final-stage (S3R) surgical procedures of choice 1,28,48. The hemodynamic advantage of one surgical template type over the other is a critical long-asked clinical question 11,29. However a definite conclusion is challenged due to patient-to-patient variations in congenital heart disease, univentricle heart function,50 preload, afterload, pulmonary, hepatic venous physiology, and respiratory pump.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of arrhythmias has come down significantly after the introduction of the total cavopulmonary connection technique. 4 Fortunately, our patient did not have an episode of arrhythmia during her entire hospital stay, nor had a history of palpitations before admission.…”
Section: Cardiac Complicationsmentioning
confidence: 78%
“…There were two hundred thirty‐nine English articles and three hundred eighty‐eight Chinese articles were initially identified (Figure ). All of the 10 articles that were finally included in the systematic review were retrospective cohort studies written in English languages. All the references of included studies were reviewed, however, none met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Nakano's study 22 did not report the exact number of people underwent ACC. Some studies 19,20,23,25 used median (quartile) approach while other studies 18,[21][22][23][24]26 used mean 6 standard deviation to report the time of CBP and ACC ( Table 2). It showed that the heterogeneity of CBP (P 5 .02, I 2 5 64%) and ACC (P < .001, I 2 5 97%) was large among groups.…”
Section: Surgical-related Eventsmentioning
confidence: 99%